PERLINDUNGAN KEPENTINGAN TERBAIK ANAK MELALUI MEDIASI NON LITIGASI DALAM SENGKETA HAK ASUH ANAK PASCA PERCERAIAN - Nurmalia Tara; Mhd Yadhi Harahap; Abd Mukhsin (El-Ahli : Jurnal Hukum Keluarga Islam, 2026)
This study is based on the increasing number of child custody (hadhanah) disputes after divorce in Indonesia, which highlights the limitations of litigation-based dispute resolution, particularly in terms of time, cost, and the psychological impact on children. Therefore, there is a need for alternative dispute resolution mechanisms that are more oriented toward the best interests of the child. This study aims to analyze out-of-court child custody dispute resolution within the Indonesian legal system and to assess the effectiveness of non-litigation mediation based on the child’s best interests through a case study of Non-Litigation Mediation Deed Number 078/AKTA-MED/LMKN-JKT/V/2024 issued by the Lembaga Mediasi Keluarga Nusantara (LMKN) Jakarta. The research method used is normative-empirical legal research with a statutory approach and case study analysis. The data are analyzed through the study of positive legal norms, legal doctrines, and the practice of child custody dispute resolution through non-litigation mediation. The findings show that the Indonesian legal system has provided a fairly comprehensive legal foundation for Alternative Dispute Resolution (ADR) mechanisms through Law No. 1 of 1974 on Marriage, the Compilation of Islamic Law (KHI), Law No. 35 of 2014 on Child Protection, and Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution. There are five forms of ADR used in child custody disputes, namely negotiation, family mediation, conciliation, customary deliberation, and institutional counseling. The LMKN case study demonstrates that a child-inclusive mediation model involving a psychologist co-mediator can produce more comprehensive agreements, including the application of joint legal custody with primary physical custody and a parenting schedule that is more adaptive to the child’s needs. The findings also indicate that the joint legal custody model combined with primary physical custody can be integrated with the concept of hadhanah in Islamic law, particularly within the framework of maqāṣid al-sharī’ah and the principle of child welfare (maslahah al-walad), and is therefore not contrary to Islamic law as long as it prioritizes the best interests of the child. This study concludes that child psychology-based non-litigation mediation is an effective dispute resolution model; however, it still faces challenges such as the absence of a specific family mediation regulation, low public literacy regarding ADR, and the limited number of certified mediators.